Banking and monetary studies - Carson, Deane; United States (Homewood, Ill. : Richard D. Irwin, 1963)
This essays commemorate evolution in the landmark establishment of a National banks by Congress in 1863 and it presents a collection of essays that would represent the interests, thinking, and methodology of monetary economists.
"A project of the Department of Banking and Economic Research, Office of the Comptroller of the Currency [in commemoration of the centennial of the national banking system]"
Includes bibliographical footnotes.
asm 23/01/2019
Loans
Keywords: Banks and banking